Behcet's Disease With Cerebral Artery Infarction Caused by Cerebral Arteritis as an Early Symptom Only With Elevated Interleukin-8 - Yin, Hao; Song, Yun; Zheng, Meimei; Han, Ju; Tang, Jiyou (Frontiers in Neurology, 2019)
Background: Behcet’s disease (BD) is a multi-systemic vasculitis which generally characterized by oral and genital ulcers as well as ocular and skin lesions. There are only 5% of BD patients get neurological involvement and it usually occurs 4-6 years later after the initial symptoms. Early onset of neurological impairment makes it difficult to diagnose and treat definitely. Case presentation: A 38-year-old man was admitted to our hospital with numbness and weakness of the left extremities. Diffusion MRI revealed focal infarction in the posterior limb of internal capsule. Skin pathology suggested small vessel vasculitis and high resolution magnetic resonance imaging revealed cerebral arteritis. He performed a negative skin pathery test but developed a scar at the venous puncture site for the intravenous fluid infusion at the early stage of disease. Laboratory examination showed the increase of IL-8. We treated the patient with an immunosuppressive agent mycophenolate mofetil (MMF), hydroxychloroquine and colchicine. Now, patients still insist on taking immunosuppressive agents, all symptoms were alleviated after treatment, rash decreased in the past six months, no acute stroke, no recurrence of oral ulcer. Conclusion: This case demonstrates that neurological involvement might be the early symptom of Behcet’s disease, and IL-8 could act as a novel target for the treatment of BD theoretically, perhaps proving to be the key to recovery.